Pengaruh Brand Image, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Pangan Bulog : Studi Kasus Konsumen Bulog Di Kelurahan Sukaringin Bekasi Utara - Nurisnaini Putri; Hadita Hadita; Neng Siti Komariah (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to analyze the influence of brand image, price and product quality on purchasing decisions. The research method used in this research is a quantitative method. The respondents in this research were Bulog consumers in Sukaringin Village, North Bekasi. The population in this study are customers who have consumed or are currently consuming Bulog rice. This sampling technique uses the Accidental Sampling method which is calculated using the Hair formula. Based on calculations using the Hair formula, it can be concluded that the number of samples obtained was 180 samples. The data used in this research is primary data, namely by distributing questionnaires. The measurement scale used is the Likert scale. The data analysis technique used in this research uses the Statistical Package for the Social Sciences (SPPS) with the help of SPSS version 26 software. The results of the research show that the brand image variable has a partially positive and significant influence on purchasing decisions, the price variable has a partially positive and significant influence on purchasing decisions, the product quality variable has a partially positive and significant influence on purchasing decisions.